2020
DOI: 10.3390/cancers13010088
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling Lipids in the Transition from Chronic Liver Disease to Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a worldwide health problem. HCC patients show a 50% mortality within two years of diagnosis. To better understand the molecular pathogenesis at the level of lipid metabolism, untargeted UPLC MS—QTOF lipidomics data were acquired from resected human HCC tissues and their paired nontumor hepatic tissues (n = 46). Blood samples of the same HCC subjects (n = 23) were compared to chronic liver disease (CLD) (n = 15) and healthy control (n = 15) blood samples. The participants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 80 publications
2
28
1
Order By: Relevance
“…In turn, in a NASH-associated HCC mouse model, reduced levels of FFAs 18:3 n-3, 20:5 n-3, 22:6 n-3, and 18:2 n-6 were found [92]. An untargeted lipidomic analysis revealed that the blood levels of almost all lipid groups were decreased in HCC patients when compared to CLD subjects and that many specific lipid classes were upor dowregulated in HCC patients with respect to healthy controls [45]. Other research showed significantly lower levels of PCs, PSs, and PIs in the serum of HCC patients [93].…”
Section: Hepatocellular Carcinoma and Lipid Alterationsmentioning
confidence: 90%
See 3 more Smart Citations
“…In turn, in a NASH-associated HCC mouse model, reduced levels of FFAs 18:3 n-3, 20:5 n-3, 22:6 n-3, and 18:2 n-6 were found [92]. An untargeted lipidomic analysis revealed that the blood levels of almost all lipid groups were decreased in HCC patients when compared to CLD subjects and that many specific lipid classes were upor dowregulated in HCC patients with respect to healthy controls [45]. Other research showed significantly lower levels of PCs, PSs, and PIs in the serum of HCC patients [93].…”
Section: Hepatocellular Carcinoma and Lipid Alterationsmentioning
confidence: 90%
“…The complex lipids (which all, except steroids non-esterified with FAs, contain FA in their structure) also have diagnostic potential. Ismail et al [45] performed untargeted lipidomic analysis in blood samples, detecting more than 500 significantly different lipid species when patients with CLD were compared to healthy controls. Notably, TAG, PCs, and plasmalogens were the most significantly upregulated lipid species in the blood of CLD patients with respect to the controls.…”
Section: Circulating Fas As Potential Biomarkers Of Nafldmentioning
confidence: 99%
See 2 more Smart Citations
“…Ceramide as the central molecule of sphingolipid metabolism has been reported to play a pro-apoptotic and anti-proliferative role in chronic liver diseases such as NASH [70], alcoholic steatohepatitis [71], and hepatic ischemia reperfusion injury [59]. Recently, the turnover from ceramide to its downstream sphingolipids such as sphigosine-1-phosphate emerge as novel diagnostic biomarkers and therapeutic targets for HCC [72].…”
Section: Discussionmentioning
confidence: 99%